2022
DOI: 10.1186/s12893-022-01847-x
|View full text |Cite
|
Sign up to set email alerts
|

One-stage posterior surgery combined with anti-Brucella therapy in the management of lumbosacral brucellosis spondylitis: a retrospective study

Abstract: Background This study aimed to assess the clinical efficacy of one-stage posterior surgery combined with anti-Brucella therapy in the treatment of lumbosacral brucellosis spondylitis (LBS). Methods From June 2010 to June 2020, the clinical and radiographic data of patients with LBS treated by one-stage posterior surgery combined with anti-Brucella therapy were retrospectively analyzed. The visual analogue scale (VAS), Japanese Orthopaedic Associati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…The lesions might slowly invade the articular surface of the vertebrae body and resulted in the proliferation and hardening of the articular surface when the anti-Brucella therapy was not intervened timely. The biomechanical structure stability of the intervertebral joint and spine sagittal balance might be destroyed if the progression continued [10]. In this study, the VAS of all patients decreased signi cantly after operation (average: 5.83 ± 1.05).…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…The lesions might slowly invade the articular surface of the vertebrae body and resulted in the proliferation and hardening of the articular surface when the anti-Brucella therapy was not intervened timely. The biomechanical structure stability of the intervertebral joint and spine sagittal balance might be destroyed if the progression continued [10]. In this study, the VAS of all patients decreased signi cantly after operation (average: 5.83 ± 1.05).…”
Section: Discussionmentioning
confidence: 54%
“…The spine is one of the most common sites of brucellosis infection, which is called brucella spondylitis (BS) [9]. Lumbosacral is the common region of the spinal brucella spondylitis, with an incidence of 2%-53%, especially L4-L5 level, and L5-S1 level [8,10], mainly manifested as spondylitis, discitis, myelitis or epidural abscess [11]. When conservative treatment fails, spinal abscess, spinal collapse, bone destruction, spinal cord compression, radiculopathy or spinal instability, surgical treatment is necessary [3,12].…”
Section: Introductionmentioning
confidence: 99%
“…[ 19 ] Furthermore, prolonged posterior landing times can worsen the occurrence of postoperative complications, such as pneumonia caused by falls and venous thrombosis in the lower extremities. [ 20 ] The findings of a previous systematic review by Joaquim [ 21 ] demonstrated that posterior laminectomy is an effective method for fixing the posterior column of the vertebral body, although it destroys the ligament complex between the support and the spinous process. While posterior internal fixation and intervertebral fusion can increase the stability of the diseased vertebrae, they also reduce mobility between vertebral bodies, which can exacerbate the incidence of adjacent spondylopathy.…”
Section: Discussionmentioning
confidence: 99%
“…(1) Standard tube agglutination test (SAT) titer ≥1:160, positive rose bengal plate test (RBT), (2) intractable low back pain with or without nerve or spinal cord compression, (3) abscess formation in the paravertebral area, lumbaris major muscle or spinal canal, (4) Bone destruction characterized by small cavities, limited amount of necrotic bone, or large necrotic bone and cavities, (5) Complete availability of all case data and follow-up information.…”
Section: Inclusion and Exclusion Criteria 221 Inclusion Criteriamentioning
confidence: 99%
“…If there are symptoms such as spinal instability, kyphosis deformity, neurological compression, or uncontrollable pain caused by the lesions, drug treatment may not significantly alleviate the symptoms. In such cases, surgical treatment can significantly improve symptoms, effectively control the progression of the disease, increase the cure rate, and reduce relapse ( 5 , 6 ). Therefore, this study analyzed clinical data of pure drug treatment, drug treatment-based posterior-only vertebral fusion, and posterior or anterior lesion clearance fusion in the treatment of lumbar brucella spondylitis.…”
Section: Introductionmentioning
confidence: 99%